(untitled) - Nissenson, Allen R. (Norwalk, Connecticut, 1995)
The best reference on end-stage renal disease! This authoritative resource has been thoroughly revised for physicians caring for the rapidly growing population of renal patients, in an expanding number of dialysis centers. Written by world-class experts, it provides coverage of essential new techniques in peritoneal dialysis, home dialysis, pediatric dialysis, and more.
Keywords: Hemodialysis,Peritoneal dialysis,Continuous ambulatory peritoneal dialysis,Hemodialysis,Kidney Failure, Chronic,Peritoneal Dialysis; Therapy